Protective Effects of Luteolin on Diabetic Nephropathy in STZ-Induced Diabetic Rats - Wang, Guo Guang; Lu, Xiao Hua; Li, Wei; Zhao, Xue; Zhang, Cui (Evidence-based complementary and alternative medicine, 2011)
Diabetic nephropathy is a long-term complication of diabetic mellitus. Many experimental evidences suggest that persistent hyperglycaemia generates intracellular reactive oxygen species (ROS) and upregulates transforming growth factor-b1 and extracellular matrix expression in mesangial and tubular epithelial cells, which is involved of free radicals in the pathogenesis of diabetes and more importantly in the development of diabetic complications. Antioxidants effectively inhibit high-glucose- and H2O2-induced transforming growth factor-b1 and fibronectin upregulation, thus providing evidence that ROS play an important role in high glucose-induced renal injury. The flavonoid luteolin has been shown to possess direct antioxidant activity, therefore we hypothesize that it may be useful in treatment of many chronic disease associated with oxidative stress, such as diabetic nephropathy via its antioxidant properties. Our results suggested that protection against development of diabetic nephropathy by luteolin treatment involved changes in superoxide dismutase (SOD) activity, the malondialdehyde (MDA) content and expression of Heme Oxygenase-1 (HO-1) protein.